Factors Associated with Coping Strategies among Primigravida Pregnant Women in Jakarta - Vivi Silawati; Afrizal; Nursyirwan Effendi; Masrul; Retno Widowati; Triana Indrayani; Andi Imam Arundhana (Journal of Pharmacy and Nutrition Sciences, 2019)
Stress in women, before and during pregnancy, may result in a negative impact on the mother and fetus. In Indonesia, the anxiety rate in primigravida pregnant women when facing labor is higher than multigravida. Every pregnant woman makes an attempt to overcome or manage stress in her pregnancy in order to adapt and cope with stress. To find out the coping ability, pregnant women should find the source of stress prior to labor. This study was conducted to determine the direct and indirect factors affecting the coping ability in primigravida pregnant women. The study used a cross sectional study method through PLS analysis. The study population consisted of primigravida pregnant women, and a sample of 200 of them was taken. The measurement results of Path Coefficients and TStatistics on the influence of variables in the structural model and overall variables showed a positive and significant effect. The T statistic value of all variables was above the critical value (1.96). The results of the PLS test indicated that the empowerment and social support variables, directly and indirectly, influenced the coping abilities. Trust, personality, lifestyle, perceptions, and attitudes had impacts directly on the coping abilities. The percentage of the direct and indirect influence between variables was 97.92%. Empowerment, social support, personality, lifestyle, perceptions, and attitudes variables had an influence on the coping abilities of primigravida pregnant women. A controlled trial study should be done to see the impact of this model on reducing the risks during pregnancy.